La Patinoire de Jean-Philippe Toussaint au miroir de La ricotta de Pier Paolo Pasolini : convergences divergentes dans une chambre d’échos - Margareth Amatulli (MediAzioni)
Jean-Philippe Toussaint’s La Patinoire is inspired by Pasolini’s La ricotta, according to the words of the Belgian writer-director. A catoptric anamorphosis connects the two cinematic works, and the contrasting dialectic that drives the Pasolinian short film allows for a deeper reading of Toussaint’s film. Through an analysis of the divergent convergences between La Patinoire and La ricotta, we will demonstrate Toussaint’s critique of the film industry, as well as the homage that the writer pays to Italian auteur cinema.